Anti‐Cortactin Autoantibodies Are Associated With Key Clinical Features in Adult Myositis But Are Rarely Present in Juvenile Myositis. Issue 2 (26th December 2021) - Pinal‐Fernandez, Iago; Pak, Katherine; Gil‐Vila, Albert; Baucells, Andres; Plotz, Benjamin; Casal‐Dominguez, Maria; Derfoul, Assia; Martinez‐Carretero, Maria Angeles; Selva‐O'Callaghan, Albert; Sabbagh, Sara; Casciola‐Rosen, Livia; Albayda, Jemima; et al.
Abstract : Objective: To define the prevalence and clinical phenotype of anti‐cortactin autoantibodies in adult and juvenile myositis. Methods: In this longitudinal cohort study, anti‐cortactin autoantibody titers were assessed by enzyme‐linked immunosorbent assay in 670 adult myositis patients and 343 juvenile myositis patients as well as in 202 adult healthy controls and 90 juvenile healthy controls. The prevalence of anti‐cortactin autoantibodies was compared among groups. Clinical features of patients with and those without anti‐cortactin autoantibodies were also compared. Results: Anti‐cortactin autoantibodies were more common in adult dermatomyositis (DM) patients (15%; P = 0.005), particularly those with coexisting anti–Mi‐2 autoantibodies (24%; P = 0.03) or anti–NXP‐2 autoantibodies (23%; P = 0.04). In adult myositis, anti‐cortactin was associated with DM skin involvement (62% of patients with anti‐cortactin versus 38% of patients without anti‐cortactin; P = 0.03), dysphagia (36% versus 17%; P = 0.02) and coexisting anti–Ro 52 autoantibodies (47% versus 26%; P = 0.001) or anti‐NT5c1a autoantibodies (59% versus 33%; P = 0.001). Moreover, the titers of anti‐cortactin antibodies were higher in patients with interstitial lung disease (0.15 versus 0.12 arbitrary units; P = 0.03). The prevalence of anti‐cortactin autoantibodies was not different in juvenile myositis patients (2%) or in any juvenile myositis subgroup compared to juvenile healthy controls (4%). Nonetheless, juvenile myositis patients with these autoantibodies had a higher prevalence of "mechanic's hands" (25% versus 7%; P = 0.03), a higher number of hospitalizations (2.9 versus 1.3; P = 0.04), and lower peak creatine kinase values (368 versus 818 IU/liter; P = 0.02) than those without anti‐cortactin. Conclusion: The prevalence of anti‐cortactin autoantibodies is increased in adult DM patients with coexisting anti–Mi‐2 or anti–NXP‐2 autoantibodies. In adults, anti‐cortactin autoantibodies are associated with dysphagia and interstitial lung disease.